Performance evaluation of a new counter flow double pass solar air heater with turbulators. (October 2018) - Abdullah, A.S.; Abou Al-sood, M.M.; Omara, Z.M.; Bek, M.A.; Kabeel, A.E.
Highlights: A counter flow double pass SAH has been proposed with two new modifications. Installing aluminum cans to the absorbing plate for improving the heater efficiency. Three absorbing plates were tested, flat plate, cans in aligned and staggered shapes. Guide blades are attached to the entrance region for ensuring well air distribution. The maximum daily efficiency was about 68%, at 0.05 kg/s for the staggered DPSAH. Abstract: Performances of the new Double Pass Solar Air Heater (DPSAH) with and without turbulators has been studied experimentally in the present investigation. Aluminum cans are attached to the upper and lower surface of the absorber plate and used as turbulators to enhance the heater efficiency. Effects of aluminum cans on Nusselt number and pressure drop of SAHs have been investigated. In addition, guide blades are attached to DPSAH entrance for ensuring adequate air distribution over the surface of the absorber which in turns enhancing the performance. Each case is compared with another Single Pass Solar Air Heater (SPSAH) at the same time. The air mass flow rate range is from 0.02 kg/s to 0.05 kg/s. Three variously designed absorber plates for DPSAH are tested: (a) flat plate absorber without cans, (b) absorber with cans in aligned configuration, (c) and the third one contains cans arranged in a staggered configuration. The purpose of the aluminum cans is to create turbulence intensity in the flow field and enlarge the heat transfer area of DPSAHs; hence, and consequently enhance heat transfer rate. Results showed that the maximum daily efficiency was 68% at 0.05 kg/s for the staggered DPSAH.